Promoting Resilience and Stress Management Strategies in Nursing Education: A Comprehensive Review of Interventions - Al Osaimi, Aysha Humood. Mohammad; Alshadidi, Faris Mohammed; ALALYANI, OMAR ALI ABDULLAH; Asiri, Dafer Ali Dafer; Almutairi, Farraj Hasan; Akelly, Hanaa Abdo; Moaidy , Jaber Ali Mohammad; Almutairi , Maha Matar; Harashy, NAHARE Jaber Yahya; Tomihg, Ali Hamad Mohd; Alshaigi , Wejdan Abdullah Mousa; Jobahe, Fairouz Hassan Ahmaed; et al. (Journal of Ecohumanism, 2024)
Background: Resilience in nursing is increasingly recognized as a vital attribute that enables healthcare professionals to cope with stressors and challenges in demanding environments. Understanding how to promote resilience is essential for mitigating burnout and enhancing job satisfaction among nurses. This study reviews various interventions aimed at fostering resilience in nursing education, particularly in light of the challenges posed by the COVID-19 pandemic. Methods: A review was conducted, analyzing 18 randomized controlled trials focused on resilience interventions for nurses. The literature was sourced from databases including CINAHL, Cochrane Library, Embase, Medline, and Scopus, employing various keywords related to resilience, coping strategies, and nursing interventions. The effectiveness of digital and face-to-face resilience training methods was evaluated, considering their immediate, short-term, and long-term impacts. Results: The findings indicated that digital resilience interventions demonstrated short-term efficacy, particularly at the 4–5-month follow-up. In contrast, face-to-face interventions did not yield significant improvements in resilience outcomes. The results suggest that while digital methods provide immediate benefits, their long-term effectiveness requires further investigation. A notable aspect of the study was the identification of the need for tailored interventions that consider individual preferences and learning styles. Conclusion: This review highlights the importance of developing context-specific resilience training programs for nurses. Digital interventions may offer flexible, accessible solutions that can enhance resilience in the short term; however, sustained support and monitoring are necessary to maximize their effectiveness. Future research should focus on larger sample sizes and interdisciplinary approaches to enhance the understanding and application of resilience-building strategies in nursing practice